2000
DOI: 10.1159/000029501
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Computed Tomography in Cases with Environmental Exposure to Asbestos in Turkey

Abstract: Background and Objectives: Although all parts of the lung can be affected as a consequence of asbestos exposure, most CT protocols tend to scan only the middle and lower parts of the thorax. The aim of this study was to investigate parenchymal and pleural lesions of persons exposed to environmental asbestos, using a high-resolution computed tomography (HRCT) protocol scanning the whole thorax. Methods: We analyzed the chest radiographs and HRCT scans of 26 patients who presented bilaterally with multiple pleur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…As in other studies (1), we found that pleural biopsy by needle was the most useful technique for the pathological diagnosis of MM (71.6%). Cytological examination had much less diagnostic value, in agreement with others (3,22).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As in other studies (1), we found that pleural biopsy by needle was the most useful technique for the pathological diagnosis of MM (71.6%). Cytological examination had much less diagnostic value, in agreement with others (3,22).…”
Section: Discussionsupporting
confidence: 89%
“…In Turkey, this disease is common in people born or living in certain villages in the central and the southeastern regions of the country (2,3).…”
mentioning
confidence: 99%
“…It is used as a whitewash material for the walls and floors of the houses, and this procedure is repeated every year. Thus, householders are repeatedly exposed to asbestos fibers in their environment, from an early age [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Since in the modern world people tend to move around it is also a necessity for doctors in other countries to be aware of the existence of specific medical problems in their patients’ home country. It is in this light that the article by Professor Topcu and his coworkers in this issue of Respiration [1]should be seen. …”
Section: Introductionmentioning
confidence: 99%